Implementation of Good Governance in Passport and Residence Permit Services at Ngurah Rai Bali Immigration. - Herlis Fahmil Qur'ani; Fedianty Augustinah; Eny Hartati (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This study examines the implementation of Good Governance principles in passport and residence permit services at Ngurah Rai Immigration Office, Bali. Employing a qualitative case study approach, the research evaluates how digital transformation enhances transparency, accountability, efficiency, participation, and the rule of law in immigration services. Findings demonstrate that digital systems such as the M-Paspor application and the Integrated Residence Permit System have improved procedural transparency, reduced illegal levies, and strengthened public trust. Efficiency has increased through automation, which reduces processing times and human errors. Digital audit trails reinforce accountability by ensuring decisions are traceable and regulation-based. However, challenges exist in substantive accountability and responsiveness. Decision-making in non-standard cases lacks transparency, with limited explanation of the legal bases. Response times through formal channels such as hotlines often exceed standards due to lengthy cross-divisional coordination. Whilst digitalisation has brought significant improvements, further reforms are necessary to strengthen substantive accountability and responsiveness, thereby enhancing public trust and institutional legitimacy in accordance with good governance standards. Continuous improvements in integrated digital systems, staff training, and process streamlining remain essential for full compliance.